In Vivo Efficacy of Bacillus velezensis Isolated from Korean Gochang Bokbunja Vinegar against Carbapenem-Resistant Klebsiella pneumoniae Infections - Ghorbanian Fatemeh; Seo Hoonhee; Tajdozian Hanieh; Lee Youngkyoung; Rahim MD Abdur; Kim Sukyung; Jung Il-Yun; Lee Saebim; Song Ho-Yeon (Polish Journal of Microbiology, 2022)
Outbreaks of carbapenem-resistant Enterobacteriaceae (CRE), especially Klebsiella pneumoniae (CRKP), are commonly reported as severe infections in hospitals and long-term care settings, and their occurrence is increasing globally. Conventional antibiotics used for treating CRE have become ineffective due to resistance development. Furthermore, their safety issues restrict their availability and use for CRE treatment. Therefore, developing new drugs different from existing drugs to combat this deadly menace is urgently needed. Probiotics can be a potential option in this context, as probiotics’ efficacy against a variety of infectious illnesses has already been well established. Here, we report the effect of the Bacillus velezensis strain isolated from Gochang Bokbunja vinegar in Korea on CRE infection using two mouse models. Data showed that pretreatment with B. velezensis significantly reduced body weight loss and mortality of CRKP-infected mice in the preventive model. The oral administration of B. velezensis in a therapeutic model also decreased the mortality and illness severity in CRKP-infected mice. Moreover, a two-week oral acute toxicity assay in guinea pigs did not reveal any aberrant clinical signs. Our findings demonstrate the potential effectiveness of our candidate probiotic strain, B. velezensis, against CRKP, suggesting that it could be used as an antimicrobial agent for treating CRKP-related infections.